Polyurea-imide prepolymer and PEEK / PTFE self-lubricating fiber fabric composite material as well as preparation and application thereof
Through the design of polyurea-imide prepolymer and PEEK/PTFE self-lubricating fiber fabric composite, the problem of poor bonding performance of bearing pad materials under high speed conditions is solved, and efficient friction reduction effect is achieved and extended The service life of the bearing.
Patent Information
- Application Number
- CN202411296755.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-09-18
AI Technical Summary
The existing bearing pad materials are difficult to withstand high friction heat and stress concentration under high-speed operating conditions, and the bonding performance of fluoro-containing polyimide resins with normal pressure curing is not ideal, and they cannot effectively reduce friction lubrication.
Using polyurea-imide prepolymer and PEEK/PTFE self-lubricating fiber fabric composite material, the fluorine element and alkyl chain are introduced through the polymerization reaction of diamine, isocyanate and dianhydride, to design the micro-phase separation structure and improve the resin Adhesion and tribological properties and green preparation using bio-based organic solvents.
The polyurea-imide resin with excellent bonding and high temperature resistance was achieved under normal pressure, which significantly improved the mechanical and tribological properties of fiber fabric composites, and extended the use stability and service life of moving parts. .
Smart Images

Figure CN119320496A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lubricating materials, in particular to a polyurea-imide prepolymer and a PEEK / PTFE self-lubricating fiber fabric composite material and preparation and application thereof. Background Art
[0002] Bearings are very important basic components in mechanical equipment. Their main function in the equipment is to support transmission and reduce the friction resistance of contacting moving parts during relative motion. With the rapid development of high-tech equipment, the service environment and operating conditions of bearings are becoming more and more demanding. Fiber fabric reinforced polymer-based composite materials have unique advantages such as low thickness, excellent dimensional stability, strong load-bearing capacity and high designability. As a lubricating layer in bearings, they have been widely used in aviation, aerospace, shipbuilding and other fields.
[0003] In recent years, the demand for high-speed resistant self-lubricating gaskets has been increasing day by day. Under high-speed operation conditions, the gasket material must be able to withstand higher friction heat and stress concentration, which requires the material to have better thermal stability and wear resistance. At the same time, most bearings are three-dimensional curved surfaces, so self-lubricating fabric gaskets are mostly hand-laid and cured at normal pressure or low pressure. In order to meet the performance requirements of gasket materials, the selection of polymer substrates for fiber fabric composite materials is very important. Polyimide resin has the advantages of high temperature resistance and strong mechanical properties, among which fluorine-containing polyimide can have better high temperature resistance. However, when the fluorine content in the molecular chain is too high, the polymer molecule will have a large electronegativity, which will break during the imidization process, showing no adhesion, and the fabric cannot be pasted to the bearing wall to achieve friction reduction and lubrication; even if the fluorine content is low, the bonding performance of fluorine-containing polyimide cured at normal pressure is not ideal. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a composite material of polyurea-imide prepolymer and PEEK / PTFE self-lubricating fiber fabric and its preparation and application. The polyurea-imide prepolymer prepared by the present invention has both excellent bonding performance and high temperature resistance, and can make the PEEK / PTFE self-lubricating fiber fabric have excellent bonding tensile performance and tribological performance.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a polyurea-imide prepolymer, comprising the following steps:
[0007] The diamine, diisocyanate and organic solvent are mixed to carry out polymerization reaction to obtain a diamine-terminated urea-containing small molecule;
[0008] The diamine-terminated urea-containing small molecule is mixed with a dianhydride for polycondensation to obtain the polyurea-imide prepolymer; at least one of the diamine and the dianhydride contains fluorine, and the diisocyanate contains an alkyl chain.
[0009] Preferably, the diamine includes one or more of 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 2,2'-bis(trifluoromethyl)diaminobiphenyl, 2,2-bis(4-aminophenyl)hexafluoropropane, 2,2-bis(3-(3-aminobenzamido)-4-hydroxyphenyl)hexafluoropropane, 2-(4-aminophenyl)-5-aminobenzimidazole, 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone and diphenyl diamine.
[0010] Preferably, the diisocyanate includes one or more of hexamethylene diisocyanate, isophorone diisocyanate, trans-1,4-cyclohexyl diisocyanate and lysine diisocyanate; and the molar ratio of the diisocyanate to the diamine is (0.1-1.0):1.0.
[0011] Preferably, the dianhydride includes one or more of pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride and hexafluoroisopropylphthalic anhydride; the molar ratio of the dianhydride to the diamine is (0.1-1.0):1.0.
[0012] Preferably, the organic solvent includes one or more of N,N-dimethylacetamide, N,N-dimethylformamide, dimethyl sulfoxide, N-methylpyrrolidone, dihydrolevoglucose, dimethyl isosorbide, soybean oil fatty acid methyl ester, lactic acid ester and D-limonene.
[0013] Preferably, the polymerization reaction temperature is 50-60° C., and the time is 5-9 h; the polycondensation reaction temperature is 0-5° C., and the time is 10-14 h; and both the polymerization reaction and the polycondensation reaction are carried out under a protective atmosphere.
[0014] The present invention provides a polyurea-imide prepolymer prepared by the preparation method described in the above technical scheme.
[0015] The present invention provides a PEEK / PTFE self-lubricating fiber fabric composite material, comprising a PEEK / PTFE self-lubricating fiber fabric and a polyurea-imide resin composited on the PEEK / PTFE self-lubricating fiber fabric, wherein the polyurea-imide resin is cured by the polyurea-imide prepolymer described in the above technical solution.
[0016] The present invention provides a method for preparing the PEEK / PTFE self-lubricating fiber fabric composite material described in the above technical solution, comprising the following steps:
[0017] Impregnating a PEEK / PTFE self-lubricating fiber fabric in the polyurea-imide prepolymer to obtain a PEEK / PTFE self-lubricating fiber fabric prepreg;
[0018] The PEEK / PTFE self-lubricating fiber fabric prepreg is bonded to the surface of a substrate and cured to obtain the PEEK / PTFE self-lubricating fiber fabric composite material.
[0019] The present invention provides the application of the PEEK / PTFE self-lubricating fiber fabric composite material described in the above technical solution or the PEEK / PTFE self-lubricating fiber fabric composite material prepared by the preparation method described in the above technical solution in the field of lubrication.
[0020] The present invention provides a method for preparing a polyurea-imide prepolymer, comprising the following steps: mixing a diamine, a diisocyanate and an organic solvent for polymerization reaction to obtain a diamine-terminated urea-containing small molecule; mixing the diamine-terminated urea-containing small molecule with a dianhydride for polycondensation reaction to obtain the polyurea-imide prepolymer; at least one of the diamine and the dianhydride contains a fluorine element, and the diisocyanate contains an alkyl chain. The present invention designs resin soft and hard segments by biomimetic dragonfly wing structure, introduces urea groups into the molecular chain of fluorinated polyimide by adding diisocyanate, thereby improving the bonding performance of the resin, and the diamine and dianhydride in the polyimide are the hard segments of the molecular chain, and the diisocyanate containing an alkane chain is the soft segment of the molecular chain, so that the design can achieve microphase separation, and the microphase separation structure can significantly improve the mechanical properties and thermal stability of the material. The polyurea-imide prepolymer prepared by the invention is prepared and cured under normal pressure, and has excellent bonding performance and high temperature resistance, and can significantly improve the mechanical properties and tribological properties of the fiber fabric self-lubricating composite material.
[0021] Furthermore, the present invention achieves the replacement of highly toxic solvents with bio-based green organic solvents (dihydro-levulinic acid ketone, isosorbide dimethyl ether, soybean oil fatty acid methyl ester, lactic acid ester and D-limonene) without affecting the properties of the generated resin, which can reduce the adverse effects on the environment and human health and achieve green preparation of polyurea-imide resin.
[0022] The present invention provides a PEEK / PTFE self-lubricating fiber fabric composite material, comprising a PEEK / PTFE self-lubricating fiber fabric and a polyurea-imide resin composited on the PEEK / PTFE self-lubricating fiber fabric, wherein the polyurea-imide resin is solidified by the polyurea-imide prepolymer described in the above technical solution. The PEEK / PTFE self-lubricating fiber fabric composite material provided by the present invention has excellent mechanical and tribological properties, and has excellent friction and wear properties under light load and high speed conditions. As a lubricating layer, it can extend the use stability and service life of moving parts. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 ATR-FTIR spectra of the PURI-DMI precursor and PURI-DMI resin obtained in Example 1 and the PURI-DMAc precursor and PURI-DMAc resin obtained in Example 2;
[0024] Figure 2 The viscosity-temperature curves of the PURI-DMI precursor obtained in Example 1 and the PURI-DMAc precursor obtained in Example 2;
[0025] Figure 3 is the tensile strength of PURI-DMI obtained in Example 1 and PURI-DMAc obtained in Example 2;
[0026] Figure 4 is the bonding strength of PURI-DMI obtained in Example 1 and PURI-DMAc obtained in Example 2;
[0027] Figure 5 The average friction coefficient of the PURI-DMI obtained in Example 1 and the PURI-DMAc obtained in Example 2 in the friction and wear performance test at different rotation speeds;
[0028] Figure 6 The average wear rate of the PURI-DMI obtained in Example 1 and the PURI-DMAc obtained in Example 2 subjected to friction and wear performance tests at different rotation speeds (both loads were 12.48 MPa);
[0029] Figure 7 SEM photos of the wear surfaces of different samples (scale is 500 μm). Figure 7Among them, (a) is the wear surface photo of PURI-DMAc at 360 r / min, (b) is the wear surface photo of PURI-DMI at 360 r / min, (c) is the wear surface photo of PURI-DMAc at 600 r / min, (d) is the wear surface photo of PURI-DMI at 600 r / min, (e) is the wear surface photo of PURI-DMAc at 800 r / min, and (f) is the wear surface photo of PURI-DMI at 800 r / min;
[0030] Figure 8 The friction coefficient and wear rate of the PURICOOH-DMAc composite material obtained in Comparative Example 1 under different working conditions. DETAILED DESCRIPTION
[0031] The present invention provides a method for preparing a polyurea-imide prepolymer, comprising the following steps:
[0032] The diamine, diisocyanate and organic solvent are mixed to carry out polymerization reaction to obtain a diamine-terminated urea-containing small molecule;
[0033] The diamine-terminated urea-containing small molecule is mixed with a dianhydride for polycondensation to obtain the polyurea-imide prepolymer; at least one of the diamine and the dianhydride contains fluorine, and the diisocyanate contains an alkyl chain.
[0034] In the present invention, unless otherwise specified, the raw materials involved are commercially available products well known in the art.
[0035] The invention mixes diamine, diisocyanate and an organic solvent to carry out polymerization reaction to obtain diamine-terminated urea-containing small molecules.
[0036] In the present invention, at least one of the diamine and the subsequent dianhydride contains fluorine, preferably trifluoromethyl. In the present invention, the diamine preferably includes one or more of 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 2,2'-bis(trifluoromethyl)diaminobiphenyl, 2,2-bis(4-aminophenyl)hexafluoropropane, 2,2-bis(3-(3-aminobenzamido)-4-hydroxyphenyl)hexafluoropropane, 2-(4-aminophenyl)-5-aminobenzimidazole, 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone and diphenyl diamine. In the present invention, the diisocyanate contains an alkyl chain, which plays a role in providing a soft segment for the molecular chain and increasing the distance of the fluorine-containing group. In the present invention, the diisocyanate preferably includes one or more of hexamethylene diisocyanate, isophorone diisocyanate, trans-1,4-cyclohexyl diisocyanate and lysine diisocyanate. In the present invention, the molar ratio of the diisocyanate to the diamine is preferably (0.1-1.0):1.0, more preferably 0.5:1.0.
[0037] In the present invention, the organic solvent preferably includes one or more of N,N-dimethylacetamide (DMAc), N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), N-methylpyrrolidone (NMP), dihydrolevoglucose ketone (Cyrene), dimethyl isosorbide (DMI), soybean oil fatty acid methyl ester, lactate and D-limonene, wherein N,N-dimethylacetamide, N,N-dimethylformamide, dimethyl sulfoxide and N-methylpyrrolidone are low toxic organic solvents, and dihydrolevoglucose ketone, dimethyl isosorbide, soybean oil fatty acid methyl ester, lactate and D-limonene are green bio-based organic solvents. The present invention focuses on the possibility of replacing standard highly toxic solvents with bio-based type solvents without affecting the properties of the resulting resin. Currently, the use of environmentally friendly solvents is a coveted goal to reduce the impact on the environment and the adverse effects of classic solvents on human health; in particular, the use of green solvents can reduce the safety hazards of fire and explosion, the health hazards of acute and chronic toxicity, and the environmental risks of air and water pollution. In addition, the use of bio-based solvents produced from renewable resources avoids the development of fossil resources, thereby limiting the emission of carbon dioxide to the environment. The present invention has no special requirements on the amount of the organic solvent, as long as the raw materials are dissolved and the reaction proceeds smoothly. In the embodiment of the present invention, the mass of the organic solvent is preferably 2.5 to 4 times the total mass of the diamine and dianhydride.
[0038] In the present invention, the polymerization reaction temperature is preferably 50-60°C, more preferably 55-60°C, and the time is preferably 5-9h, more preferably 6-8h; the polymerization reaction is preferably carried out under a protective atmosphere, and the protective atmosphere is preferably nitrogen.
[0039] In the present invention, the specific operation of the polymerization reaction is preferably:
[0040] Adding the diamine into the organic solvent, stirring and dissolving, to obtain a diamine solution;
[0041] The diamine solution is heated to 50-60° C., and a protective atmosphere is introduced into the reaction container. Then, diisocyanate is slowly added dropwise into the diamine solution to carry out a polymerization reaction.
[0042] In the present invention, the diisocyanate is preferably added at a rate of 1 drop / min. When the diisocyanate is solid, the diisocyanate is preferably dissolved in a solvent before the addition is performed; the polymerization reaction time is calculated from the completion of the addition of the diisocyanate. In the present invention, the diisocyanate is slowly added dropwise to avoid self-polymerization of the isocyanate. After the polymerization reaction is completed, a diamine-terminated urea-containing small molecule is obtained, and no post-treatment is required, and the next step of the reaction is directly performed.
[0043] After obtaining the diamine-terminated urea-containing small molecule, the present invention mixes the diamine-terminated urea-containing small molecule with dianhydride for polycondensation to obtain the polyurea-imide prepolymer.
[0044] In the present invention, the dianhydride preferably includes one or more of pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-diphenyl ethertetracarboxylic dianhydride and hexafluoroisopropylphthalic anhydride; the molar ratio of the dianhydride to the diamine is preferably (0.1-1.0):1.0, more preferably 0.5:1.0. In the present invention, the diisocyanate provides the soft segment in the molecular chain, and the diamine and dianhydride provide the hard segment.
[0045] In the present invention, the temperature of the polycondensation reaction is preferably 0-5°C, the time is preferably 10-14h, more preferably 12-13h; the polycondensation reaction is preferably carried out under a protective atmosphere, and the protective atmosphere is preferably nitrogen.
[0046] In the present invention, the specific operation of the polycondensation reaction is preferably:
[0047] Dissolving the dianhydride in a solvent to obtain a dianhydride solution; the solvent is the same as the organic solvent described in the above technical solution;
[0048] The diamine-terminated urea-containing small molecule is cooled to 0-5° C., and the dianhydride solution is added dropwise thereto under stirring and a protective atmosphere to carry out a polycondensation reaction.
[0049] In the present invention, the dripping rate of the dianhydride solution is preferably 1 mL·min -1 The polycondensation reaction time is calculated from the completion of the dropwise addition of the dianhydride solution. After the polycondensation reaction, no post-treatment is required to obtain the polyurea-imide prepolymer.
[0050] Polyimide resin has the advantages of high temperature resistance and strong mechanical properties, but its bonding performance is not as good as that of polyurethane, phenolic resin and other resins; and although polyurethane has excellent bonding performance, its high temperature resistance is poor. The present invention is inspired by the distribution of soft and hard segments of dragonfly wings and provides a method for synthesizing a polyurea-imide prepolymer, that is, diisocyanate is introduced into the resin as a soft segment, and fluorine-containing diamine and dianhydride are used as hard segments, which can not only avoid the fluorine element causing the resin to have weak or no adhesion, but also construct a microphase separation structure, thereby enhancing the mechanical properties, thermal stability, conductivity, etc. of the resin. The present invention realizes the preparation of fluorine-containing high temperature resistant and excellent bonding performance polyurea-imide prepolymers under normal pressure.
[0051] The present invention provides a polyurea-imide prepolymer prepared by the preparation method described in the above technical solution. In the present invention, the polyurea-imide prepolymer contains urea groups and amide bonds. The polyurea-imide prepolymer provided by the present invention has both excellent bonding performance and high temperature resistance.
[0052] The present invention provides a PEEK / PTFE self-lubricating fiber fabric composite material, comprising a PEEK / PTFE self-lubricating fiber fabric and a polyurea-imide resin composited on the PEEK / PTFE self-lubricating fiber fabric, wherein the polyurea-imide resin is cured by the polyurea-imide prepolymer described in the above technical solution.
[0053] The present invention has no special requirements for the PEEK / PTFE self-lubricating fiber fabric, and it can be prepared by using commercial products or by a preparation method well known to those skilled in the art. In an embodiment of the present invention, the weaving method of the PEEK / PTFE self-lubricating fiber fabric is twill, wherein the surface density ratio of PTFE fiber to PEEK fiber is 2:1.
[0054] The present invention provides a method for preparing the PEEK / PTFE self-lubricating fiber fabric composite material described in the above technical solution, comprising the following steps:
[0055] Impregnating a PEEK / PTFE self-lubricating fiber fabric in the polyurea-imide prepolymer to obtain a PEEK / PTFE self-lubricating fiber fabric prepreg;
[0056] The PEEK / PTFE self-lubricating fiber fabric prepreg is bonded to the surface of a substrate and cured to obtain the PEEK / PTFE self-lubricating fiber fabric composite material.
[0057] The present invention impregnates the PEEK / PTFE self-lubricating fiber fabric in the polyurea-imide prepolymer to obtain a PEEK / PTFE self-lubricating fiber fabric prepreg. In the present invention, the viscosity of the polyurea-imide prepolymer is preferably 0.2 to 0.8 Pa·s. When the viscosity of the polyurea-imide prepolymer is large, before impregnation, the polyurea-imide prepolymer is preferably diluted with a solvent to a viscosity of 0.2 to 0.8 Pa·s; the solvent is preferably the same as the organic solvent described in the above technical solution. In the present invention, the impregnation is preferably repeated. After each impregnation, the impregnated fabric is preferably placed in an oven at 60 to 70°C (preferably 65 to 70°C) for drying, and then the next impregnation is performed; the number of impregnations is based on the mass proportion of the PEEK / PTFE self-lubricating fiber fabric in the PEEK / PTFE self-lubricating fiber fabric prepreg reaching 65 to 70%.
[0058] After obtaining the PEEK / PTFE self-lubricating fiber fabric prepreg, the present invention bonds the PEEK / PTFE self-lubricating fiber fabric prepreg to the surface of the substrate and solidifies it to obtain the PEEK / PTFE self-lubricating fiber fabric composite material. In the present invention, the adhesive used for the bonding is the polyurea-imide prepolymer (without additional dilution), that is, the substrate and the self-lubricating fiber fabric composite material are chemically bonded by the polyurea-imide prepolymer (as an adhesive). In the present invention, the substrate preferably includes a steel substrate or a titanium alloy substrate, and the steel substrate preferably includes a bearing steel substrate.
[0059] In the present invention, the curing procedure preferably includes: heating from room temperature to 80°C at a heating rate of 3-5°C / min, and keeping warm for 2h; then heating to 100°C at a heating rate of 3-5°C / min, and keeping warm for 1h; then heating to 150°C at a heating rate of 3-5°C / min, and keeping warm for 1h; then heating to 180°C at a heating rate of 2-5°C / min, keeping warm for 1h, and finally naturally cooling to room temperature; the curing is carried out under normal pressure. The present invention adopts gradient temperature curing to ensure that the material can fully react and cure at different temperature sections, while avoiding internal stress and defects caused by too fast heating, and finally obtaining a polyimide material with stable performance. The present invention controls the curing temperature of the last stage at 180°C, which can avoid molecular chain breakage (the temperature is too high, and the urea group will break and reorganize), while satisfying the imidization of polyimide. In addition, although the fluorine-containing polyimide resin in the prior art can provide high temperature resistance, its molding process requires hot pressing, which is not suitable for the molding process of the existing bearing self-lubricating fabric curved surface parts, while the curing described in the present invention can be carried out under normal pressure.
[0060] The present invention provides the application of the PEEK / PTFE self-lubricating fiber fabric composite material described in the above technical solution or the PEEK / PTFE self-lubricating fiber fabric composite material prepared by the preparation method described in the above technical solution in the field of lubrication. The PEEK / PTFE self-lubricating fiber fabric composite material provided by the present invention has excellent bonding tensile properties and tribological properties, and has excellent friction and wear properties under light load and high speed conditions, and can extend the use stability and service life of moving parts (such as bearings) using the fiber fabric self-lubricating composite material as a lubricating layer.
[0061] To further illustrate the present invention, the polyurea-imide prepolymer and PEEK / PTFE self-lubricating fiber fabric composite material provided by the present invention and their preparation and application are described in detail below in conjunction with examples, but they should not be construed as limiting the scope of protection of the present invention.
[0062] In each of the embodiments and comparative examples, the weaving method of the PEEK / PTFE self-lubricating fiber fabric is twill, wherein the surface density ratio of the PTFE fiber to the PEEK fiber is 2:1.
[0063] Example 1
[0064] First, 5.5474 g (0.0107 mol, 2 equivalents) of 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane (HFBAPP) was dissolved in 20 mL of dimethyl isosorbide (DMI) under stirring, heated to 60 ° C in a water bath, and high-purity nitrogen was introduced into the reaction vessel. Subsequently, 0.8999 g (0.00535 mol, 1 equivalent) of hexamethylene diisocyanate was added dropwise to the reaction vessel. After reacting for 8 hours, the reaction vessel containing the reactants was transferred to an ice water bath at 0-5 ° C, and a high-purity nitrogen atmosphere was also required. Then 1.7239 g (0.00535 mol, 1 equivalent) of 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA) was dissolved in 15 mL of DMI and stirred at 1 mL min -1 After 12 hours of reaction, a polyurea-imide prepolymer (PURI-DMI precursor) was obtained.
[0065] The PURI-DMI precursor was diluted with DMI to a viscosity of 0.5 Pa·s. Then, the PEEK / PFTE blended fabric was repeatedly immersed in the PURI-DMI precursor dilution solution, and after each immersion, it was dried in an oven at 65°C before the next immersion. The PEEK / PFTE blended fabric accounted for 65-70% of the total mass, and the PEEK / PTFE prepreg was obtained.
[0066] PEEK / PTFE prepreg was pasted to the surface of 45# steel using PURI-DMIprecursor, and the sample was placed in a muffle furnace for curing. The curing procedure was to heat to 80°C in 20 minutes and keep it warm for 2 hours; then heat to 100°C within 5 minutes and keep it warm for 1 hour; then heat to 150°C and 180°C within 15 minutes, and keep each temperature section for 1 hour; finally, the sample was naturally cooled to room temperature in the muffle furnace to obtain a PEEK / PTFE self-lubricating fiber fabric composite material, recorded as PURI-DMI. PURI-DMIprecursor was dripped onto a glass sheet and cured at the same curing temperature as above, and then the film was separated from the glass sheet to obtain a polyurea-imide resin, recorded as PURI-DMI resin.
[0067] Example 2
[0068] First, 5.5474 g (0.0107 mol, 2 equivalents) of 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane (HFBAPP) was dissolved in 20 mL of N,N-dimethylacetamide (DMAc) under stirring, heated to 60 ° C in a water bath, and high-purity nitrogen was introduced into the reaction vessel. Subsequently, 0.8999 g (0.00535 mol, 1 equivalent) of hexamethylene diisocyanate was added dropwise to the reaction vessel. After reacting for 8 hours, the reaction vessel containing the reactants was transferred to an ice water bath at 0-5 ° C, and a high-purity nitrogen atmosphere was also required. Then 1.7239 g (0.00535 mol, 1 equivalent) of BTDA was dissolved in 15 mL of DMAc and heated at 1 mL min -1 After 12 hours of reaction, polyurea-imide prepolymer (PURI-DMAc precursor) was obtained.
[0069] The PEEK / PFTE blended fabric is repeatedly impregnated in the PURI-DMAc precursor, and after each impregnation, it is dried in an oven at 65° C. before the next impregnation, until the PEEK / PFTE blended fabric accounts for 65-70% of the total mass, thereby obtaining a PEEK / PTFE prepreg.
[0070] The PEEK / PTFE prepreg was pasted to the surface of 45# steel, and the sample was placed in a muffle furnace for curing. The curing procedure was to heat up to 80°C in 20 minutes and keep it warm for 2 hours; then heat up to 100°C within 5 minutes and keep it warm for 1 hour; then heat up to 150°C and 180°C within 15 minutes, and keep each temperature section for 1 hour; finally, the sample was naturally cooled to room temperature in the muffle furnace to obtain a PEEK / PTFE self-lubricating fiber fabric composite material, recorded as PURI-DMAc. The PURI-DMAc precursor was drop-coated on a glass sheet and cured at the same curing temperature as above, and then the film was separated from the glass sheet to obtain a polyurea-imide resin, recorded as PURI-DMAc resin.
[0071] Comparative Example 1
[0072] First, 4.1606g (0.008025mol, 3 / 2 equivalent) of 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane (HFBAPP) was dissolved in 20mL N,N-dimethylacetamide (DMAc) under stirring, heated to 60°C in a water bath, and high-purity nitrogen was introduced into the reaction vessel. After that, 0.4070g (0.002675mol, 1 / 2 equivalent) of 3,5-diaminobenzoic acid (DABA) was added to the reaction vessel until DABA was completely dissolved. Subsequently, 0.8999g (0.00535mol, 1 equivalent) of hexamethylene diisocyanate was added dropwise to the reaction vessel. After reacting for 8h, the reaction vessel containing the reactants was transferred to an ice water bath at 0-5°C, which also required a high-purity nitrogen atmosphere. Then 1.7239 g (0.00535 mol, 1 equivalent) of BTDA was dissolved in 15 mL of DMAc and stirred at 1 mL min -1 After 12 hours of reaction, polyurea-imide prepolymer (PURICOOH-DMAcprecursor) was obtained.
[0073] The PEEK / PFTE blended fabric is repeatedly impregnated in the PURICOOH-DMAc precursor, and after each impregnation, it is dried in an oven at 65° C. before the next impregnation, until the PEEK / PFTE blended fabric accounts for 65-70% of the total mass, thereby obtaining a PEEK / PTFE prepreg.
[0074] The PEEK / PTFE prepreg was pasted to the surface of 45# steel, and the sample was placed in a muffle furnace for curing. The curing procedure was to heat up to 80°C in 20 minutes and keep it warm for 2 hours; then heat up to 100°C within 5 minutes and keep it warm for 1 hour; then heat up to 150°C and 180°C within 15 minutes, and keep each temperature section for 1 hour; finally, the sample was naturally cooled to room temperature in the muffle furnace to obtain a PEEK / PTFE self-lubricating fiber fabric composite material, recorded as PURICOOH-DMAc. The PURICOOH-DMAc precursor was drop-coated on a glass sheet and cured at the same curing temperature as above, and then the film was separated from the glass sheet to obtain a polyurea-imide resin, recorded as PURICOOH-DMAc resin.
[0075] Example 3
[0076] First, 3.4265g (0.0107mol, 2 equivalents) of 2,2'-bis(trifluoromethyl)diaminobiphenyl was dissolved in 20mL of dihydro-levorotatory glucosone (Cyrene) under stirring, heated to 60°C in a water bath, and high-purity nitrogen was introduced into the reaction vessel. Subsequently, 0.8999g (0.00535mol, 1 equivalent) of hexamethylene diisocyanate was added dropwise to the reaction vessel. After reacting for 8 hours, the reaction vessel containing the reactants was transferred to an ice water bath at 0-5°C, which also required a high-purity nitrogen atmosphere. Then 1.7239g (0.00535mol, 1 equivalent) of BTDA was dissolved in 15mL of Cyrene and stirred at 1mL min -1 The reaction mixture was added dropwise to the above reactants at a rate of 1.5 %. After reacting for 12 hours, a polyurea-imide prepolymer (PURI-Cyreneprecursor) was obtained.
[0077] The PEEK / PFTE blended fabric is repeatedly impregnated in the PURI-Cyrene precursor, and after each impregnation, it is dried in an oven at 65°C before the next impregnation, until the PEEK / PFTE blended fabric accounts for 65-70% of the total mass, thereby obtaining a PEEK / PTFE prepreg.
[0078] The PEEK / PTFE prepreg was pasted to the surface of 45# steel, and the sample was placed in a muffle furnace for curing. The curing procedure was to heat up to 80°C in 20 minutes and keep it warm for 2 hours; then heat up to 100°C within 5 minutes and keep it warm for 1 hour; then heat up to 150°C and 180°C within 15 minutes, and keep each temperature section for 1 hour; finally, the sample was naturally cooled to room temperature in the muffle furnace to obtain a PEEK / PTFE self-lubricating fiber fabric composite material, recorded as PURI-Cyrene. The PURI-Cyreneprecursor was dripped onto a glass sheet and cured at the same curing temperature as above, and then the film was separated from the glass sheet to obtain a polyurea-imide resin, recorded as PURI-Cyrene resin.
[0079] Example 4
[0080] First, 3.5766g (0.0107mol, 2 equivalents) of 2,2-bis(4-aminophenyl)hexafluoropropane was dissolved in 20mL of dimethyl isosorbide (DMI) under stirring, heated to 60°C in a water bath, and high-purity nitrogen was introduced into the reaction vessel. Subsequently, 0.8999g (0.00535mol, 1 equivalent) of hexamethylene diisocyanate was added dropwise to the reaction vessel. After reacting for 8 hours, the reaction vessel containing the reactants was transferred to an ice water bath at 0-5°C, which also required a high-purity nitrogen atmosphere. Then 1.7239g (0.00535mol, 1 equivalent) of BTDA was dissolved in 15mL of DMI and stirred at 1mL min -1 After 12 hours of reaction, a polyurea-imide prepolymer (PURI-DMI-1precursor) was obtained.
[0081] The PEEK / PFTE blended fabric is repeatedly impregnated in the PURI-DMI-1precursor, and after each impregnation, it is dried in an oven at 65°C before the next impregnation, until the PEEK / PFTE blended fabric accounts for 65-70% of the total mass, thereby obtaining a PEEK / PTFE prepreg.
[0082] The PEEK / PTFE prepreg was pasted to the surface of 45# steel, and the sample was placed in a muffle furnace for curing. The curing procedure was to heat up to 80°C in 20 minutes and keep it warm for 2 hours; then heat up to 100°C within 5 minutes and keep it warm for 1 hour; then heat up to 150°C and 180°C within 15 minutes, and keep each temperature section for 1 hour; finally, the sample was naturally cooled to room temperature in the muffle furnace to obtain a PEEK / PTFE self-lubricating fiber fabric composite material, recorded as PURI-DMI-1. PURI-DMI-1precursor was dripped onto a glass sheet and cured at the same curing temperature as above, and then the film was separated from the glass sheet to obtain a polyurea-imide resin, recorded as PURI-DMI-1resin.
[0083] Performance testing and structural characterization
[0084] Figure 1 The ATR-FTIR spectra of PURI-DMI precursor and PURI-DMI resin obtained in Example 1 and PURI-DMAc precursor and PURI-DMAc resin obtained in Example 2. -1 The peaks near 2930cm are caused by -NH- vibration. -1 and 2850cm -1 The peak at 1719cm is due to the asymmetric and symmetric vibration of CH in -CH2-.-1 and 1783cm -1 The peak at 1200-1324 cm is due to the vibration of C=O. The vibration of trifluoromethyl (-CF3) in HFBAPP is at 1200-1324 cm -1 The spectra of PURI-DMI precursor and PURI-DMAc precursor are compared with those of PURI-DMI resin and PURI-DMAc resin, with a peak at 3500-2730 cm -1 There is a broad scattering peak at , which is caused by OH in the precursor. After thermal imidization, the imine ring is formed and -OH is removed, so the scattering peak disappears in PURI-DMIresin and PURI-DMAc resin.
[0085] The viscosity-temperature curves of PURI-DMI precursor and PURI-DMAc precursor were tested using the Austrian Anton Paar MCR 302 rheometer. The resin viscosity during hand lay-up molding is usually controlled between 0.2Pa·s and 0.8Pa·s. The viscosity within this range helps ensure that the resin can fully wet the fiber while avoiding the flow phenomenon caused by too low viscosity. Figure 2 The viscosity-temperature curves of PURI-DMI precursor and PURI-DMAc precursor are shown in Figure 2. Figure 2 It can be seen that the viscosity of PURI-DMIprecursor is relatively high. At 25°C, the viscosity of PURI-DMIprecursor is 9.596Pa·s, which is much higher than the ideal viscosity. Therefore, it is necessary to dilute PURI-DMIprecursor with DMI solvent to make its viscosity within the ideal range. The viscosity of PURI-DMAcprecursor is 0.39Pa·s at 25°C, so it can be used directly.
[0086] The mechanical properties of PEEK / PTFE self-lubricating fiber fabric composites were evaluated using a universal testing machine. The specifications of each sample were 12cm×2cm, and the testing machine performed tensile tests on the fabric composites at a speed of 20mm / min. Each sample was measured 5 times, and the 3 middle values were selected to calculate the average tensile strength. The results are shown in Figure 3. The bonding strength of the fabric composites was studied using an electronic fabric strength tester (YG026D) at a crosshead speed of 20 mm / min. The impregnated fabric was cut into given sizes (length 12 cm, width 2 cm). Subsequently, the test samples were fixed on an AISI-1045 steel plate (length 60 mm, width 20 mm, adhesive length 45 mm) with the corresponding prepolymer and cured. Each sample required 5 measurements, and 3 intermediate values were taken to calculate the average bonding strength. The results are shown in Figure 4 As shown. Figure 3 and Figure 4 It can be seen that the tensile properties of PURI-DMI (188.20±3.57MPa) are slightly higher than those of PURI-DMAc (178.49±4.74MPa), while the peeling properties of PURI-DMI (1.23±0.32N / mm) are significantly higher than those of PURI-DMAc (0.82±0.09N / mm). In summary, PURI-DMI has better mechanical properties.
[0087] The friction and wear properties of PURI-DMAc or PURI-DMI composite materials were tested using a Xuanwu No. 3 friction and wear testing machine (the contact mode was pin-disc, the rotation speeds were 360 r / min, 600 r / min, 800 r / min, respectively, the load was 12.48 MPa, and the test time was 120 min). Figure 5 The average friction coefficient of the composite material is shown, and the corresponding data are shown in Table 1; Figure 6 is the average wear rate, and the corresponding data are shown in Table 2.
[0088] Table 1 Friction coefficient of PURI-DMAc and PURI-DMI composites
[0089]
[0090] Table 2 Wear rate of PURI-DMAc and PURI-DMI composites
[0091]
[0092] Depend on Figures 5-6 As can be seen from Tables 1 and 2, under the experimental conditions, PURI-DMI exhibits a lower friction coefficient and wear rate.
[0093] Figure 7 are SEM photos of the worn surfaces of different samples. Figure 7(a) is a photo of the wear surface of PURI-DMAc at 360r / min, (b) is a photo of the wear surface of PURI-DMI at 360r / min, (c) and (d) are photos of the wear surface of PURI-DMAc and PURI-DMI at 600r / min, respectively, and (e) and (f) are photos of the wear surface of PURI-DMAc and PURI-DMI at 800r / min, respectively. Among them, PURI-DMAc wears the most seriously at 600r / min, with a large number of fibers breaking and pulling out. However, when the working conditions are more severe, that is, when the speed is increased to 800r / min, the wear of PURI-DMAc and PURI-DMI is significantly reduced. This is because when the speed increases, the friction heat also increases. The polyurea-imide resin is modified on the basis of the polyimide resin, and the high-temperature tribological properties of the polyimide resin are better than those at room temperature within a certain range. Therefore, when the speed increases, the wear resistance of PURI-DMAc and PURI-DMI also improves. In other words, at high speeds, both PURI-DMAc and PURI-DMI exhibit ideal tribological properties; and at medium or low speeds, PURI-DMI also exhibits ideal tribological properties (low friction and low wear), so PURI-DMI has better mechanical and tribological properties.
[0094] Figure 8 The friction coefficient and wear rate of the PURICOOH-DMAc composite material prepared in Comparative Example 1 under different working conditions. The friction and wear performance of the PURICOOH-DMAc composite material was tested using a Xuanwu No. 3 friction and wear tester (the contact mode was pin-disc, the rotation speeds were 360r / min and 600r / min, and the test time was 120min). The corresponding values are shown in Table 3.
[0095] Table 3 Friction coefficient and wear rate of PURICOOH-DMAc composite material obtained in Comparative Example 1
[0096]
[0097] PURICOOH-DMAc resin reduces the content of -CF3 groups due to the introduction of DABA, and compared with HFBAPP, the DABA benzene ring content is lower, that is, the hard segment content of PURICOOH-DMAc decreases. Therefore, PURICOOH-DMAc does not have a microphase separation structure. Compared with PURI-DMI and PURI-DMAc with microphase separation structures, the friction coefficient of PURICOOH-DMAc decreases but the wear rate increases at 12.48MPa and 600r / min. This is because the PTFE fibers inside the fabric play a lubricating role, resulting in a decrease in its friction coefficient. PURICOOH-DMAc exhibits poor tribological properties. Therefore, the resin with a microphase separation structure constructed by the bionic dragonfly wing structure can have better tribological properties.
[0098] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing a polyurea-imide prepolymer, characterized in that: The following steps are involved: The diamine, diisocyanate and organic solvent are mixed to carry out polymerization reaction to obtain a diamine-terminated urea-containing small molecule; The diamine-terminated urea-containing small molecule is mixed with a dianhydride for polycondensation to obtain the polyurea-imide prepolymer; at least one of the diamine and the dianhydride contains fluorine, and the diisocyanate contains an alkyl chain.
2. The preparation method according to claim 1, characterized in that: The diamine includes one or more of 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 2,2'-bis(trifluoromethyl)diaminobiphenyl, 2,2-bis(4-aminophenyl)hexafluoropropane, 2,2-bis(3-(3-aminobenzamido)-4-hydroxyphenyl)hexafluoropropane, 2-(4-aminophenyl)-5-aminobenzimidazole, 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone and diphenyl diamine.
3. The preparation method according to claim 1 or 2, characterized in that: The diisocyanate includes one or more of hexamethylene diisocyanate, isophorone diisocyanate, trans-1,4-cyclohexyl diisocyanate and lysine diisocyanate; the molar ratio of the diisocyanate to the diamine is (0.1-1.0):1.
0.
4. The preparation method according to claim 1 or 2, characterized in that: The dianhydride includes one or more of pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride and hexafluoroisopropylphthalic anhydride; the molar ratio of the dianhydride to the diamine is (0.1-1.0):1.
0.
5. The preparation method according to claim 1, characterized in that: The organic solvent includes one or more of N,N-dimethylacetamide, N,N-dimethylformamide, dimethyl sulfoxide, N-methylpyrrolidone, dihydrolevoglucose, isosorbide dimethyl ether, soybean oil fatty acid methyl ester, lactic acid ester and D-limonene.
6. The preparation method according to claim 1, characterized in that: The polymerization reaction temperature is 50-60° C., and the time is 5-9 hours; the polycondensation reaction temperature is 0-5° C., and the time is 10-14 hours; and both the polymerization reaction and the polycondensation reaction are carried out under a protective atmosphere.
7. The polyurea-imide prepolymer prepared by the preparation method according to any one of claims 1 to 6.
8. A PEEK / PTFE self-lubricating fiber fabric composite material, characterized in that: It comprises a PEEK / PTFE self-lubricating fiber fabric and a polyurea-imide resin compounded on the PEEK / PTFE self-lubricating fiber fabric, wherein the polyurea-imide resin is formed by curing the polyurea-imide prepolymer according to claim 7.
9. The method for preparing the PEEK / PTFE self-lubricating fiber fabric composite material according to claim 8, characterized in that: The following steps are involved: Impregnating a PEEK / PTFE self-lubricating fiber fabric in the polyurea-imide prepolymer to obtain a PEEK / PTFE self-lubricating fiber fabric prepreg; The PEEK / PTFE self-lubricating fiber fabric prepreg is bonded to the surface of a substrate and cured to obtain the PEEK / PTFE self-lubricating fiber fabric composite material.
10. Use of the PEEK / PTFE self-lubricating fiber fabric composite material according to claim 8 or the PEEK / PTFE self-lubricating fiber fabric composite material prepared by the preparation method according to claim 9 in the field of lubrication.
Citation Information
Patent Citations
Self-lubricating elastic wear-resistant polyimide composite material and preparation method thereof
CN104031387A
Preparation method of polyimide fiber / polytetrafluoroethylene fiber self-lubricating fabric liner material
CN111844968A
Polyurea-polyimide random block copolymer as well as preparation method and application thereof
CN114854008A
Polyurea / polyimide copolymer self-lubricating composite material suitable for wide temperature range and preparation method of polyurea / polyimide copolymer self-lubricating composite material
CN115160783A
Environment-friendly polyimide insulating paint as well as preparation method and application thereof
CN117903685A